Pengaruh Social Media Marketing terhadap Penciptaan Identitas Brand: Studi Kasus Perusahaan Teknologi - Fauzi, Aprian; Qizwini, Jimmi (STIE Perbankan Indonesia, 2024)
This study aims to explore the influence of social media marketing on brand identity creation with a case study on technology companies Gojek and Tokopedia. Amidst the rapid development of digital technology, social media marketing has become a crucial strategy in building and strengthening brand identity, especially in competitive sectors such as technology. The method used in this study is descriptive qualitative. Data were collected through in-depth interviews with stakeholders in both companies and analysis of social media content published by Gojek and Tokopedia. The results of the study indicate that social media plays a significant role in creating and maintaining a strong and consistent brand identity for Gojek and Tokopedia. These findings provide important insights for other technology companies on how to effectively utilize social media to build an attractive and competitive brand identity. This study also emphasizes the importance of a well-planned social media marketing strategy to achieve optimal results in brand identity creation. Keywords: Social Media Marketing, Brand Identity, Technology Company, Qualitative, Case Study